PERUBAHAN KURIKULUM DAN DAMPAK PERGANTIAN KURIKULUM13 (K13) KE KURIKULUM MERDEKA - Andini, Laili Firda; Fitria; Bashith, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The change in curriculum from Curriculum 13 to the independent curriculum has a considerable impact on education in Indonesia. This study will examine how the impact on teachers, students, and society in the future. This research uses a literature study research method, namely reviewing previous researchers related to curriculum changes. This research method allows researchers to identify, analyze, and synthesize some relevant research findings, besides that it can provide an overview of the difficulties faced by teachers, students and society. The results of this study show that the change from curriculum 13 to the independent curriculum is not as easy as imagined and has various impacts from various angles, such as implementation challenges, teacher readiness, quality of teaching materials, besides the impact provided in the form of increased creativity and thinking skills, readiness for the world of work, increased social impact.